Long-term prognosis for jumper's knee in male athletes: A prospective follow-up study - Kettunen, J. A.; Kvist, M.; Alanen, E.; Kujala, U. M. (The American Journal of Sports Medicine, 2002)
Little information is available on the long-term outcome of jumper's knee, a common problem among athletes. PURPOSE: Our aim was to determine the 15-year prognosis of jumper's knee. STUDY DESIGN: Prospective case control. METHODS: The prognosis for jumper's knee was studied using two groups: athletes with jumper's knee and nonsymptomatic control athletes. At baseline, all subjects participated in standardized clinical examinations and measurements, and 15 years later they were asked to respond to a questionnaire. RESULTS: Twenty athletes with jumper's knee and 16 athlete control subjects responded (response rate 74% and 84%, respectively). The jumper's knee group reported significantly more knee symptoms according to their Kujala score and more knee pain after repeated squatting. Fifty-three percent of the subjects in the jumper's knee group (9 of 17) reported that they had quit their sports career because of their knee problem, compared with 7% of the control athletes (1 of 14). Patellar height was associated with knee symptoms at follow-up. CONCLUSION: Jumper's knee causes mild but long-lasting symptoms after an athletic career.